2014
DOI: 10.3389/fbioe.2014.00054
|View full text |Cite
|
Sign up to set email alerts
|

Material Models and Properties in the Finite Element Analysis of Knee Ligaments: A Literature Review

Abstract: Knee ligaments are elastic bands of soft tissue with a complex microstructure and biomechanics, which are critical to determine the kinematics as well as the stress bearing behavior of the knee joint. Their correct implementation in terms of material models and properties is therefore necessary in the development of finite element models of the knee, which has been performed for decades for the investigation of both its basic biomechanics and the development of replacement implants and repair strategies for de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 125 publications
2
52
0
Order By: Relevance
“…In order to improve the understanding of their functionality, mechanical tests on animals on human specimens' samples are commonly performed 2,3 . The results of such tests, for both physiological and pathological samples, are fundamental in order to provide clinical guidelines, to identify the mechanical impact of pathologies on human joints, to check new possible rehabilitation or surgical treatments and to deliver inputs for the development of reliable biomechanical models 4,5 . Even if several studies are already present in the literature, no agreement can be currently found for the characterization of a specific soft-tissue 3,5 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to improve the understanding of their functionality, mechanical tests on animals on human specimens' samples are commonly performed 2,3 . The results of such tests, for both physiological and pathological samples, are fundamental in order to provide clinical guidelines, to identify the mechanical impact of pathologies on human joints, to check new possible rehabilitation or surgical treatments and to deliver inputs for the development of reliable biomechanical models 4,5 . Even if several studies are already present in the literature, no agreement can be currently found for the characterization of a specific soft-tissue 3,5 .…”
Section: Introductionmentioning
confidence: 99%
“…The results of such tests, for both physiological and pathological samples, are fundamental in order to provide clinical guidelines, to identify the mechanical impact of pathologies on human joints, to check new possible rehabilitation or surgical treatments and to deliver inputs for the development of reliable biomechanical models 4,5 . Even if several studies are already present in the literature, no agreement can be currently found for the characterization of a specific soft-tissue 3,5 . For example, it is recognized that ligaments are characterized by a non-linear viscoelastic behavior 5,6 which implies their mechanical properties increases along with the loading rate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this state, the ligaments are strained and therefore already sustaining a load (Galbusera et al, 2014). Our findings show the generic values for reference strain differ significantly from numerically obtained reference strain.…”
Section: Discussionmentioning
confidence: 58%